Against Red Fascism!: Anti-Communism of the Czech Antifascist Action as a Polarizing Factor on the Czech Radical Left - Charvát, Jan (PARTECIPAZIONE E CONFLITTO, 2024)
After the collapse of communism in 1989, several new phenomena emerged in the Czech Republic, including the far right, which built on aggressive anti-communism, nationalism, and support for right-wing currents. At the same time, there was a significant discrediting of general left-wing attitudes because of their identification with communism. The article focuses on how the Czech Antifascist Action (AFA) worked with anti-communism. The article first shows the basic principles on which anti-communism is based. It then focuses on post-communist anti-communism, specifically in the Czech Republic. At the same time, the article presents the history of anarchist anti-communism. The article then summarizes AFA’s history, specifically its Czech version until the COVID-19 period. Methodologically, the article uses content analysis. The crucial data source is the texts published by AFA in their magazine Antifa News or Akce! and on their website Antifa.cz. In principle, it can be assumed that anti-communism played several distinct roles but were intertwined and mutually reinforcing. It enabled AFA to distinguish itself from the Communist Party and communism generally. The specificity of the Czech AFA’s anti-communism lies in combining both approaches typical of anarchist anti-communism and approaches characteristic of the Czech variant of post-communist anti-communism.